Statement made by Jane Tolmach to the Members of the Board of Supervisors September, 1999 - Jane Tolmach:::::: (1999)
A statement made by Jane Tolmach requesting that the California Board of Supervisors approve the plan made by the Airport Authority to start over with a lowered set of operations.